Free-standing thick-film piezoelectric device - Kok, Swee Leong; White, Neil; Harris, Nick (IET, 2008)
A free-standing thick-film cantilever sensor structure is presented. Such devices find use in applications such as vibration detection or energy harvesting. The structure was fabricated by screen printing layers of lead zirconate titanate between silver/palladium electrodes and cofiring the layers together with a carbon sacrificial layer (deposited underneath) in an air environment at a temperature of 8508C. The free-standing structure, of dimensions 18 mm long by 9 mm wide and thickness of 50 mm, was found to produce electrical powers of up to 95 nW at an acceleration level of 9.81 m/s2 (1 g), when driving a 60 kV load resistance.